Early risk factors for juvenile and youthful homicide offenders in the Pittsburgh Youth Study - Farrington, David (The Routledge international handbook of juvenile homicide, 2024)
The main aim of this chapter is to study early risk factors for juvenile and youthful homicide offenders in the Pittsburgh Youth Study (PYS). The PYS is a prospective longitudinal study of 1517 males who were first studied in 1987–88 at ages 7–13. Of these males, 40 became convicted homicide offenders: eight as juveniles (ages 15-17), 23 as young adults (ages 18-20), and nine as adults (ages 21-26). In addition, 37 males were arrested for homicide but not convicted. Seven explanatory (nonbehavioral) risk factors significantly predicted juvenile homicide offenders: African American race, living in an area with a high percentage of African Americans, living in a bad neighborhood according to census data, a family with low socioeconomic status, peer delinquency, peer substance use, and having bad friends. In addition, eight behavioral risk factors significantly predicted juvenile homicide offenders: a high screening risk score, selling hard drugs, being suspended from school, cruelty to animals, carrying a gun, carrying a weapon, conduct disorder, and a positive attitude to delinquency. Early risk factors for other types of homicide offenders are also presented, and some implications for criminological theory and prevention policy are discussed.